Mithuna and maithuna figures on kumbha moulding - Temples of India Project Team (Jio Institute, 2024)
One of the mouldings on the vedibandha of the garbhagriha is the kumbha which is carved with figures of deities, apsaras, mithunas and maithunas. Here, both the mithuna and maithuna imagery can be seen. Mithuna represents a couple embracing each other where the male figure is softly pressing his partner’s breast. The maithuna, next to the couple, shows four figures engaged in amorous activities.